(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This paper analyzes the presence of writing and registering instruments in several settlements of the NE Iberian Peninsula (2nd-1st c. BC), attempting to assess their historical, cultural and economic interest, as a reflection of the process of integration within the Roman world. It also analyzes the relation between these writing instruments and the local epigraphy.